Multi-Family Ventures, LLC and the 2008 financial crisis : ethical decisions regarding keeping the board informed - Morawski, Mike; Castleberry, Stephen B. (London : NeilsonJournals Publishing, 2020)
This true account provides a summary of a firm and its CEO caught up in the housing market frenzy that occurred in the mid to late 2000s. Although confronted with a number of economic, strategic management, human resource, ethical, and legal challenges, the owners make decisions that cause the firm to grow at an exponential rate. The case documents the eventual results of many of those decisions. Readers are challenged to identify ethics issues involved and the business decisions that precipitated those ethical issues. Some issues include working with business partners who have different ethical stances from your own, whistle blowing for illegal actions, the impact of problem employees on ethical and legal issues, and being transparent and honest when informing the board of directors about business conditions. Teaching notes include lessons learned by the CEO. Ways to avoid similar mistakes in the future are provided.
Originally Published InMorawski, M., & Castleberry, S.B. (2020). Multi-Family Ventures, LLC and the 2008 Financial Crisis: Ethical Decisions Regarding Keeping the Board Informed. Journal of Business Ethics Education, 17(1), 273-284. JBEE17-0CS6.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business ethics